1986
DOI: 10.1159/000249320
|View full text |Cite
|
Sign up to set email alerts
|

The Relapses of Cystic Acne after Isotretinoin Treatment Are Age-Related: A Long-Term Follow-Up Study

Abstract: 89 patients (66 males and 23 females) with severe acne were treated with isotretinoin and were followed up for a period of 6–47 months (mean 14 months) after the end of the therapy. Relapses occurred in 14.6% of the patients. They were not found to be related to the total amount of isotretinoin administered (up to 233 mg/kg); a possible, although not significant, link to sex was observed since relapses occurred in 16.6% males and 8.6% of females. But the age of the patients had a significant bearing on the lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 3 publications
2
39
0
1
Order By: Relevance
“…Like other authors [2,3], we found a correlation with age: young patients with progressive acne relapse more readily. This is linked with the natural course of acne where there is a tendency for spontaneous cure the longer the disease persists: older patients have greater chances of being definitively cured.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Like other authors [2,3], we found a correlation with age: young patients with progressive acne relapse more readily. This is linked with the natural course of acne where there is a tendency for spontaneous cure the longer the disease persists: older patients have greater chances of being definitively cured.…”
Section: Discussionsupporting
confidence: 89%
“…However, the follow-up period was very variable. Cunliffe et al [1] and Cunliffe and Norris [2] consider patients without relapse for 2.5 years to be definitively cured; for the Germans, the follow-up period is 1 year [4,7], for Harms et al [ 3], it is from 6 to 47 months; for Amer icans it is from 12 to 18 months [6] and, finally, for the Finns it is 24 months [5]. In our study, out of 87 patients reviewed after 1 year, it is almost certain that some re lapsed.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the frequency of relapses is concerned, Harms et al [344] followed 89 patients for many months (mean 14 months) after the treatment had been stopped. They first failed to find a significant relationship between the frequency of the relapses and the total amount of isotretinoin administered.…”
Section: From Vitamin a To Isotretinoin: Innovative Views On Acne Patmentioning
confidence: 99%
“…They first failed to find a significant relationship between the frequency of the relapses and the total amount of isotretinoin administered. They suggested a possible link to sex, the relapses occurring more frequently in males [344]. Few years later, they analyzed the relapse rate related to the daily dose and to the cumulative dose in more than 200 patients [345].…”
Section: From Vitamin a To Isotretinoin: Innovative Views On Acne Patmentioning
confidence: 99%
“…On the other hand, Harms et al [7] reported that younger patients relapsed more frequently than older patients, as also did male compared to female patients. Cunliffe and Norris [8] provided an association of duration of the disease prior to isotretinoin treatment and relapse rates.…”
mentioning
confidence: 97%